A voice based text mail system for visually impaired - Mary Belinda M.J, Carmel; N, Rupavathy; N.R, Mahalakshmi (International Journal of Engineering and Technology, 2018)
To develop a voiceÂ primarily basedÂ email systemÂ that willÂ facilitateÂ visually impairedÂ individualsÂ to access emailÂ in aÂ problemÂ freeÂ Â Â manner.Â Together withÂ providing usage of mail servicesÂ simplyÂ andÂ with efficiency, the systemÂ also willÂ cut backÂ theÂ psychological Â Â Â Â Â Â Â Â featureÂ workÂ thatÂ mustÂ beÂ unremarkablyÂ taken by the visually impairedÂ to recollectÂ and sortÂ charactersÂ usingÂ the normalÂ Braille Â Â Â Â Â Â Â Â Â keyboards, which areÂ accessibleÂ to them. TheÂ graphical user interfaceÂ ofÂ this methodÂ has been evaluated against the interface of theÂ traditionally accessibleÂ mail system.Â Not only for visually impaired, but also for Â people whoÂ areÂ illiterateÂ mightÂ have the benefit ofÂ this technique.Â The foremost crucialÂ facetÂ which willÂ beÂ thought ofÂ developingÂ this techniqueÂ is that the users ofÂ this techniqueÂ does not have any basicÂ informationÂ regardingÂ the keyboard shortcuts used orÂ whereverÂ the keysÂ areÂ used for. All functions to beÂ utilized inÂ this techniqueÂ areÂ supposed to beÂ easyÂ mouse clickÂ operationsÂ creatingÂ the systemÂ veryÂ user friendly. This application Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â proposesÂ anÂ androidÂ application, designed specifically for visually impairedÂ individuals. This application provides a voiceÂ primarily basedÂ mailing serviceÂ which provides them to browseÂ and send mail on their own,Â without anyÂ guidance. The usersÂ ought toÂ useÂ certainÂ keywordsÂ which canÂ performÂ certainÂ actions for e.g. Read, Send, Compose Mail, Address Book etc. This EMAIL Â Â Â Â Â Â Â Â systemÂ isÂ utilized byÂ aÂ visually handicapped personÂ to access mailsÂ easilyÂ andÂ with efficiency.Â ThereforeÂ reliance of visually impaired onÂ othersÂ for his or her ownÂ activitiesÂ associated withÂ mailÂ are oftenÂ reduced.